Optimization’s trajectory of an automatic manipulator using neural networks - A.V., Fedossova; Santoyo, Julian (Revista Colombiana de Computación, 2008)
Neural networks are used bto optimize the trajectory of an automatic manipulator.First, it is had an automatic manipulator of three degrees of freedom. Keywords: Neural Networks, Optimizatión, Semi-infinite programming.